The Correlation Between Pre-Operative Fasting Duration and Post-Operative Nausea and Vomiting Occurrence on Patients with General Anestehesia - Karmana, Dede; Mixrova Sebayang, Septian; Kemal Firdaus, Eza; Sukmaningtyas, Wilis (Java Nursing Journal, 2024)
Background: Preoperative fasting is a procedural measure implemented before surgery or anesthesia to avert regurgitation or vomiting. PONV incidence is influenced by surgical, anesthetic, and patient-related factors. The purpose of the study is to ascertain the duration of preoperative fasting observed by participants and the prevalence of PONV according to personality traits. Purpose: Determine the correlation between the duration of preoperative fasting and the occurrence of PONV in patients undergoing general anesthesia at RSUD Dr. Soekardjo Tasikmalaya. Methods: Observatory, descriptive, and cross-sectional designs are utilized. The sampling method was with sixty respondents ranging in age from seventeen to forty-five years, ASA I to II. Data is collected via observation and evaluation. Findings: The study observed that among 37 individuals (61.7%), preoperative fasting for 6-8 hours was beneficial, while for 23 individuals (38.3%), fasting for >8 hours were detrimental. At the age of 17-25 years, 10 individuals (47.6%) develop PONV, while 11 individuals (52.4%) do so between the ages of 26-45. Among women, 17 individuals (81.0%) have PONV, while 20 individuals (95.2%) have ASA I physical status, and 1 individual (4.8%) has ASA II physical status. Conclusion: There is a significant link (p < 0.013) between preoperative fasting time and postoperative nausea and vomiting (PONV) in patients under general anesthesia. Fasting before surgery should be long enough to avoid PONV